Production and characterization of laccase and manganese peroxidase from the ligninolytic fungus Fomes sclerodermeus - Papinutti, Víctor Leandro (2006)
Fomes sclerodermeus was grown on semi-defined media based on yeast extract, peptone and glucose (YPG). The fungus produced a minimum basal level of laccase activity irrespective of culture medium. The highest laccase production (20 U cm−3) was obtained in cultures supplemented with CuSO4. Manganese peroxidase (MnP) could only be detected when MnSO4 was added to the medium. None of the aromatic compounds tested stimulated further laccase or MnP production. Laccase and MnP stimulated by Cu2+ or Mn2+ respectively were purified. Two different laccase isoenzymes with the same molecular mass (67 kDa) and N-linked carbohydrate content (3%) and a slight difference in their pI values (3.41 and 3.48) were characterized. In addition, two different MnP isoenzymes with the same molecular mass (47 kDa) and N-linked carbohydrate content (4%) and different pI values (3.35 and 3.45) were characterized. Both enzymes showed good stability at 25 °C and over a wide range of pH. Both laccases oxidize ABTS (2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) more efficiently than 2,6-dimethoxyphenol (DMP) with similar efficiency values (Kcat/Km) while the MnP I, the major peroxidase isoenzyme in the studied conditions, oxidizes the Mn2+ and Mn-mediated activity on DMP more efficiently than MnP II.